Eksistensi Haritage Hotel Di Bali: Studi Kasus Hotel Inna Bali Denpasar - I Wayan Sunarsa (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2020)
The purpose of this study is to determine the existence of Hotel Inna Bali in the development strategy that has been, is being and will be carried out to maintain its status as a historical cultural heritage building. Interview and observation techniques were used to collect data and the informan was the General Manager of Hotel Inna Bali. The results show that the strategies that have been, are being and will be carried out by the hotel management in maintaining its status as a historical cultural heritage building are (1) carrying out maintenance for the physical condition of the Cultural Heritage to remain sustainable (2) restoring the physical condition damaged buildings in accordance with the originality of materials, shapes, layouts and work techniques to extend their life (3) developing the potential value, information and promotion of cultural heritage (4) adapting, namely developing cultural heritage for activities that are more appropriate needs of the present. The challenges faced by Hotel Inna Bali as a historical cultural heritage building are (1) lack of public awareness and concern for the importance of cultural heritage which is not only in terms of art, but also in terms of historical buildings, (2) changing people's perceptions that heritage hotels are not expensive hotels, (3) you cannot carelessly make changes, renovations and revitalization of parts of the hotel building itself.